Effect of crop establishment methods and phosphorus nutrition on growth and productivity of mungbean (Vigna radiata L. Wilczek) in semi-arid Afghanistan - Ehsan, Qudratullah; Rana, D.S.; Choudhary, Anil K. (Annals of Agricultural Research, 2017)
A field experiment was conducted at Experimental Farm of Afghanistan National AgriculturalSciences and Technology University (ANASTU), Kandahar, Afghanistan during July to September,2015 comprised of 8 treatment combinations using two planting methods (broadcast and line-sowing)and four phosphorus levels (0, 30, 60 and 90 kg P2O5 ha–1) in a sandy-clay loam soil to assess thegrowth, morpho-physiological and yield parameters, and yield of mungbean in a split-plot designreplicated thrice. It was revealed that line-sowing exhibited significantly higher values of growthparameters (plant height, leaf area index, dry matter accumulation, branches plant–1), growth indices(absolute growth rate, crop growth rate, relative growth rate, net assimilation rate), root growthparameters (root dry weight plant–1, root nodules plant–1 and root length plant–1), yield attributes,and grain (1284 kg ha–1) and straw yield (2943 kg ha–1) of mungbean over broadcast-sowing. Likewise,the successive increase in phosphorus levels upto 60 kg P2O5 ha–1 resulted in significantly highergrowth attributes, growth indices, root growth parameters, yield attributes and grain and strawyield of mungbean compared to rest of the P2O5 levels. In general, the highest grain yield (1420 kgha–1) recorded with 60 kg P2O5 ha–1 which was 8.5, 7.6 and 67.5% higher over 30 kg P2O5 ha–1, 90 kgP2O5 ha–1 and control, respectively. Overall, line-sowing alongwith 60 kg P2O5 ha–1 can berecommended to harness higher growth and productivity of Kharif mungbean in semi-arid conditionsof Afghanistan.